Impact of Short Social Training on Prosocial Behaviors: An fMRI Study - Lukinova, Evgeniya; Myagkov, Mikhail (Frontiers in Systems Neuroscience, 2016)
Efficient brain-computer interfaces (BCIs) are in need for knowledge about human brain that interacts, plays games, and socializes with other brains. A breakthrough can be achieved by revealing the microfoundations of prosocial actions such as fairness, cooperation, and the public goods provision at the cost of individual gain. Building upon our previous behavioral work, we conduct a series of functional magnetic resonance imaging (fMRI) experiments to measure whether and how sociality alters the functional activation of and connectivity between the specific systems in the brain. The overarching hypothesis of this study is that sociality, even in a minimal form, serves as a natural mechanism of sustainable cooperation by fostering interaction between brain regions associated with social cognition and those related to value calculation. Sociality, or social utility, is defined as an additional component of the utility function reflecting the value of contributing to group success derived from social identity. We use group-based manipulations to induce varying levels of sociality and compare behavior in two social dilemmas: Prisoner’s Dilemma and variations of Ultimatum Game. Using fMRI gives us a unique perspective on how sociality works by allowing us to examine neural dynamics in human brain during the computation of utility in the context of strategic games that involve social interaction. We find that right inferior frontal gyrus, a region previously associated with cognitive control and modulation of the valuation system, is found to correlate with the medial prefrontal cortex (mPFC) to a greater degree when participants make economic decisions as they interacted with others in the high sociality condition compared to the low sociality condition.